Effect of Benzothiazoline Ligand and Corresponding Organoantimony(V) Derivative on the Reproductive System of Male Rats (Bioinorganic Chemistry and Applications)
Benzothiazoline H NC 6 H 4 SC ︹ ( C 6 H 5 )CH:C( OH ) COOCH 3 1 prepared by the condensation reaction of aroyl pyruvate and 2-aminothiophenol has been treated with Ph 3 Sb ( OPr i ) 2 to yield Ph 3 Sb[SC 6 H 4 NC( C 6 H 5 )CH:CO ︹ COOCH 3 ] 2 . These compounds have been characterized by elemental analyses and molecular weight determinations. The probable structures of the ligand as well as antimony complex have been tentatively proposed on the basis of IR and NMR ( H 1 and C 13 ) spectral evidences. Both compounds have been tested for their antifertility activity in male albino rats. The oral administration of compounds 1 and 2 at the dose level of 10 mg/rat/day significantly reduced the weights of testes, epididymides, ventral prostate, and seminal vesicles. The production of preleptotene spermatocytes was decreased by 36.57% ; 57.23% , pachytene spermatocytes by 40.06% ; 62.01% , and secondary spermatocytes by 52.45% ; 63.22% , following the treatment of compounds 1 and 2 , respectively. The marked reduction in sperm motility and density resulted in infertility by 100% . Significant ( P<.01 ) alterations were found in biochemical parameters of reproductive organs in treated animals as compared to control group. It is concluded that all these effects may finally impair the fertility of male rats.